2019
DOI: 10.1186/s12906-019-2648-8
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces apoptosis of benign prostatic hyperplasia epithelial cell line (BPH-1) through p38 MAPK-FOXO3a pathway

Abstract: Background Resveratrol is reported to inhibit the growth of prostate, which is characteristic of benign prostatic hyperplasia (BPH) condition. However, the mechanism remains unclear. This study aimed to identify the effects and probable mechanism of resveratrol on BPH. Methods We used the BPH epithelial cell line BPH-1 to investigate the effect of resveratrol. Cells were treated with various concentrations of resveratrol, and its effects on cells viability, apoptosis, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…It has been demonstrated that RES has many benefits such as anti-cardiovascular effect, anti-tumor effect, anti-oxidant effect, and anti-BPH effect [13,16,26]. Since previous studies have suggested that the peanut sprouts contain high amounts of RES, we investigated the content of RES in 5 types of the Korean peanut varieties (Sindae, Inhua-C, Inhua-W , Inhua-L, and Yesan) germinated for 9 days using sawdust medium fermented for 45 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that RES has many benefits such as anti-cardiovascular effect, anti-tumor effect, anti-oxidant effect, and anti-BPH effect [13,16,26]. Since previous studies have suggested that the peanut sprouts contain high amounts of RES, we investigated the content of RES in 5 types of the Korean peanut varieties (Sindae, Inhua-C, Inhua-W , Inhua-L, and Yesan) germinated for 9 days using sawdust medium fermented for 45 days.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al [15] reported that peanut sprouts contain RES, which can be a source of natural antioxidants. Several studies in BPH have suggested that RES inhibits the proliferation of prostatic cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies reported that maternal dietary resveratrol addition decreased the levels of T cell receptor genes, MAPK signal transduction pathways in weaning piglets, and it alleviated weaning-associated diarrhea and intestinal inflammatory disorders in porcine offspring [116]. Moreover, many studies have shown that this compound could potentially induce apoptosis and in vitro ROS accumulation through p38 MAPK signaling pathways [117][118][119]. Yang et al [120] also reported that resveratrol was able to reduce ROS accumulation, inflammation, and angiogenesis both in vivo and in vitro, then displaying preventive effects for rheumatoid arthritis (RA).…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…Resveratrol has been reported to have anti-proliferative effects not only in cancer cells but also in non-tumor cells, such as pulmonary artery smooth muscle cells [ 120 ]. In an in vitro study, resveratrol inhibited the growth of BPH-1 cells [ 121 ]. In short, flow cytometry indicated that apoptotic cell rates significantly increased in a concentration-dependent manner when resveratrol was administered to BPH-1 cells at various concentrations (20 and 30 μM).…”
Section: Management Of Benign Prostate Hyperplasia With Polyphenolmentioning
confidence: 99%
“…Furthermore, a Western blot analysis indicated that phosphorylated-p38 mitogen-activated protein kinase (MAPK) level significantly increased after resveratrol treatment, and the expression of Forkhead-box protein O3a (FOXO3a) and anti-apoptotic molecules, such as Bcl2 and Bcl-XL, were downregulated with increased cleaved caspase3 levels. Finally, resveratrol treatment led to enhanced cleaved caspase3 levels [ 121 ]. These results suggested that resveratrol may induce apoptosis via p38 MAPK activation and FOXO3a repression.…”
Section: Management Of Benign Prostate Hyperplasia With Polyphenolmentioning
confidence: 99%